DREAM OF CASHLESS INDIA: BENEFITS & CHALLENGES - Khurana, Bharat (International Journal of Research -GRANTHAALAYAH, 2017)
Cashless society is the concept where transactions involving money take place through digital mode and where there is no or very little use of hard cash. This research paper discusses the efforts of Government of India in promoting cashless transactions. Considering all these efforts, move towards digital India is no longer seems to remain just a dream. All over India steps are being taken to make this dream come true and the benefits that it will provide in long run are worth making these hard efforts. All these benefits have been discussed and the hurdles in path to the success of this programme have also been highlighted.